Risk Management Strategy for Murabahah Financing at Bank Sumut Syariah Rantau Prapat - Harahap, Ledis Izzah; Harahap, Muhammad Ikhsan; Jannah, Nurul (UNIVERSITAS PAKUAN, 2024)
This research aims to find out the steps in implementing murabahah financing risk management and solutions for resolving problematic financing at Bank Sumut Syariah Rantau Prapat. Qualitative research methodology was used in this research taking place at PT. Bank Sumut Syariah Rantau Prapat. Research data was collected from internal documents of Bank Sumut Syariah Rantau Prapat in the form of files, direct interviews with Bank Sumut Syariah Rantau Prapat Account Officers who handle murabahah financing and problematic financing, as well as supporting literature that is relevant to the problems raised by the researcher. The results of the research conclude that the implementation of risk management for murabahah financing at Bank Sumut Syariah Rantau Prapat has been carried out well. In handling problematic financing, Bank Sumut Syariah Rantau Prapat has several alternatives, namely, intensive billing, rescheduling, reconditioning, restructuring, and repayment by selling collateral. /partial/full guarantee.